The Smurfs tales. 1, The Smurfs and the bratty kid and other tales! - Peyo (New York : Papercutz, 2021)
"On the occasion of the all-new animated TV series starting on Nick this September, an all-new series of Smurfs graphic novels! The Smurfs are back in new stories in English for the first time! First, when Papa Smurf's stork gets wounded in a storm, he must rely on the kindness of a local farmer to nurse the stork back to flying condition. A different kind of storm arrives in the shape of Johnny, the nephew of the farmer. The boy is as aggressive as his uncle is friendly. Making his way to the Smurfs Village, Johnny leaves a path of destruction in his wake, putting the whole village in jeopardy. Plus, tales of the Smurfs on vacation! Also, there's plenty of medieval action and adventure from the king's page (and loyal ally to the Smurfs) Johan his silly sidekick, the mischievous jester Peewit, go off on an adventure featuring Papa Smurf. And, even more smurfs comic-strips to add some blue and brighten any day"--
Subtitle from cover.
Translated from the French.
Keywords: Smurfs (Fictitious characters) -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Children -- Behavior -- Comic books, strips, etc; Smurfs (Fictitious characters) -- Juvenile literature; Magic -- Juvenile literature; Children -- Juvenile literature; Graphic novels; Comic books, strips, etc; Comics (Graphic works).; Fantasy comics